Regulation of Controlled Drugs in Emerging Countries: Unique Attention to BRICS - Mahalakshmy, R. (Asian Journal of Pharmaceutics (AJP), 2017)
BRICS is an association of five major emerging national economies: Brazil, Russia, India, China, and South Africa. The BRICS members are all developing newly industrialized countries, but all are distinguished by their large, fastest-growing economies and significant influence on regional affairs; all five are G-20 members. As of 2015, the five BRICS countries represent over 3 billion people or 42% of the world population; all five members are in the top 25 of the world by population, and four are in the top 10. Previously, the emerging markets have had little commercial interest or impact on the pharmaceutical industry with their limited gross domestic product (GDP). Comparing the E7 (Brazil, China, India, Indonesia, Mexico, Russia, and Turkey) with the G7 in terms of pharmaceutical expenditure helps to highlight this. In 2004, the E7 spent 0.94% of their GDP on prescription medications compared to 1.31% by the G7, and for the same year, the E7 accounted for only 8% of the global market versus 79% by the G7. If these countries manage to reach their predicted GDP growth targets and continue to spend the same proportion of their GDP on prescription medications, then by 2020 the E7 is estimated to account for 14% of a global pharmaceutical market worth $800 billion. This demonstrates just how big of a potential the emerging markets hold for the future of the pharmaceutical industry in terms of trade and research. Regulation of controlled drugs with regulatory authorities, import - export criteria and offenses & penalties among different BRIC countries.